Mediating Role of 6V-Based SBMI Between Competitive Strategies and Firm Performance: An Empirical Study of China’s Electric Vehicle Industry - Zang, Xiaohui; Abdullah, Raja Nazim; Feng, Yi; Wu, Mingling; Lu, Yanqiu; Zhu, Enzhou; Zhang, Yingfeng (World electric vehicle journal, 2025)
Strategic management and sustainable business model innovation (SBMI) are widely recognized important firm performance. This study develops a theoretical framework that integrates competitive strategy, SBMI, and performance, with SBMI conceptualized through the multidimensional 6V model. While the model is broadly applicable across industries, this study focuses on the electric vehicle (EV) sector in China as an empirical case to test the proposed relationships. Using survey data from 261 managerial respondents across nine major Chinese EV brands, PLS-SEM is employed to examine both direct and mediated effects of differentiation and cost leadership strategies. The results confirm that both strategies positively influence firm performance; however, the mediating roles of SBMI dimensions vary. This study contributes to the literature by demonstrating the explanatory power of the 6V-SBMI framework and offering practical insights for firms seeking to align strategic choices with sustainability-oriented innovation.